PENERAPAN NUMBER HEADS TOGETHER UNTUK MENINGKATKAN STUDENTS’ ENGAGEMENT DAN HASIL BELAJAR SMKN 3 SURAKARTA - Novia Dani Pramusinto; Sri Wahyuni; Salman Alfarisy Totalia (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2016)
This research is aimed to improve students’ engagement and students’ learning achievement through implementation of Number Heads Together at SMKN 3 Surakarta 2015/2016 academic year. The subject of this research is the students of X Marketing II class of SMKN 3 Surakarta. The techniques of collecting the data used in this research are questionnaire, observation, interview, documentation and test. The procedures of this research are planning, acting, observing and reflecting. The result of the research showed that students’ engagement in the pre-cycle was 29.03%, improved in the 1st cycle up to 77.42% and in the 2nd cycle up to 90.32%. The result of the students’ achievement in cognitive aspect of the pre-cycle was 6.25%, improved up to 75.86% in the 1st cycle and 79.31% in the 2nd cycle. The result of the students’ achievement in affective aspect of the pre-cycle was 81.25%, improved in the 1st cycle up to 83.87% and in the 2nd cycle was 87.10%. The result of the students’ achievement in psychomotor aspect of the pre-cycle was 78.13%, improved in the 1st cycle up to 80.65% and 86.21% in the 2nd cycle. Based on the result of this research, it can be concluded that the implementation of Number Heads Together can improve students’ engagement and students’ learning achievement in the subject of Introduction of Economy and Business of X Marketing II class of SMKN 3 Surakarta 2015/2016 academic year.